2004
DOI: 10.1590/s1516-635x2004000400004
|View full text |Cite
|
Sign up to set email alerts
|

Boron supplementation in broiler diets

Abstract: Boron supplementation in broiler feed is not a routine practice. However, some reports suggest a positive effect of boron on performance. This study assessed the effects of boron supplementation on broiler performance. Diets were based on maize and soybean meal, using boric acid P.A. as boron source. Six supplementation levels (0, 30, 60, 90, 120 and 150 ppm) were evaluated using 1,440 one-day old males housed at a density of 30 chickens in each of 48 experimental plots of 3m². A completely randomized block de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 4 publications
4
11
3
Order By: Relevance
“…In agreement with our findings, Fassani et al (2004) reported that birds fed with a diet of 30 ppm boron consumed 140 g less feed than the 0 ppm group while exhibiting better feed conversion and similar mortality rates. However, the specific depressive effect regarding dietary boron supplementation on the feed intake of broilers was barely occasioned with the dietary levels of 300 ppm or more (Rossi et al, 1993).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our findings, Fassani et al (2004) reported that birds fed with a diet of 30 ppm boron consumed 140 g less feed than the 0 ppm group while exhibiting better feed conversion and similar mortality rates. However, the specific depressive effect regarding dietary boron supplementation on the feed intake of broilers was barely occasioned with the dietary levels of 300 ppm or more (Rossi et al, 1993).…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, dietary boron supplementation did not improve mineral retention in soft tissues and bone, except for the boron concentration. Our results are in accord with several authors who reported no benefits in the bone ash and Ca concentration of broilers in response to boron supplementation of 20 to 150 mg/kg (Fassani et al, 2004;Çınar et al, 2015). However, others have reported significant increases in tibia Ca concentration (Armstrong et al, 2000;Kurtoğlu et al, 2005;Bozkurt et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Fassani et al (2004) reported that chickens fed with a diet of 30 ppm boron consumed 140 g less feed than controls while exhibiting lower FCR and without compromising weight gain and livability. In contrast, Bozkurt et al (2012) reported that 30 and 60 ppm boron supplementation tended to increase feed intake.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, dietary boron supplementation did not affect P concentrations in the tibia and femur. The increased bone ash content of the hens corresponds with that of some studies (Qin & Klandorf, 1991;Wilson & Ruszler, 1997;Rossi et al, 1993b;Kurtoğlu et al, 2005), but not in others (Wilson & Ruszler 1998;Fassani et al, 2004). Wilson & Ruszlar (1998) observed that the addition of 50, 100, 200 and 400 mg boron/kg to layer diets decreased bone Ca and P concentrations while Fassani et al (2005) observed no response in bone Ca concentration when 30, 60, 90, 120 and 150 mg boron/kg were added to a broiler diet.…”
Section: Resultsmentioning
confidence: 69%